Evaluasi Derajat Homogenisasi (Homodegree) dan Korelasinya dengan Ukuran Partikel Lemak Susu Sterilisasi Komersil - Azis Boing Sitanggang; Azizah Luthfiyah Assa’adiyah; Dahrul Syah (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2019)
Homogenization is one of the key processes in the production of UHT milk. This process is designed to reduce the size of fat globule, thus decreases the possibility of milk fat separation during storage. To ease the monitoring of successful homogenization process, homogenization degree (homodegree, oH) is commonly used instead of direct measurement of fat globule size using particle size analyser (PSA). This study was aimed to investigate the correlation between the resulted homodegree and the results of particle size analysis using PSA. There were two UHT milk variants used, A and B. Within this study, UHT milk fat globule of variant A dan B had mean diameter of 0.314 ± 0.020 μm and 0.228±0.005 μm, respectively. By this, a higher value of oH was resulted from UHT milk variant A. The homodegree was sensitive respective to the change of particle size of UHT milk for each variant. Additionally, homodegree was found to have a poor correlation, i.e., based on coefficient of determination (R2) especially for smaller size of fat globules (d10). However, this correlation was evaluated to increase for larger fat globules (d50, d90). Homodegree was also found to have poor correlation either with pressure or inlet temperature applied in homogenization. Despite some miscorrelation found between the homodegree and pressure or temperature of homogenization, measuring homodegree below 13.5 was still found sufficient to indicate successful homogenization in which UHT milk fat globule size was below 0.4 μm. Keywords: fat globule, homodegree, homogenization, particle size analysis, UHT milk